ENGRAVING “BURIAL OF COUNT FEDOR GOLOVIN” FROM THE FUND COLLECTION OF THE NATIONAL KYIV-PECHERSK HISTORICAL AND CULTURAL RESERVE (City: History, Culture, Society, 2021)
The study is devoted to the engraving in the historical context of the engraving from the fund collection of the National Kyiv-Pechersk Historical and Cultural Reserve.The considered work of engraving art shows the funeral procession of Count Fedor Golovin (1650–1706), Russian “Chancellor”. Golovin died in the summer of 1706 in Glukhiv, on the way to Kyiv. His death was a landmark event for the domestic and foreign policy of the Moscow kingdom and was reflected in Russian-Ukrainian relations. That is why the death and funeral of Golovin were recorded in many sources, some of which are given in the article along with engraving.The print question is dated to the 19th century, although it is made from a board of the 18th century. The author of the board is an unknown engraver, most likely of foreign origin. Perhaps the work was performed in the workshop of one of the Dutch engravers who worked at that time in Russia. Possible authors include Adrian Schonebeck and Peter Picart. However, this assumption requires further refinement.The visual series of the engraving contains a number of characteristics of the mourning culture of the Baroque era. The author of the article investigated individual motifs displayed in the engraving (representation of heraldic symbols, stylized antique images, the theme of chivalry, and so on).A comparative analysis of the image of the funeral procession of Fedor Golovin with the funeral of other Russian statesmen of that time reflected in the sources was carried out. Also in this series were added the funeral of Emperor Peter I.It is noted that the traditions presented in the work gravitate to the Polish-gentry concept of pompa funebris. In turn, it could have been borrowed by the Russians from the Cossack foreman of the Hetman State.In addition, the study outlines the prospects for studying such works as sources for Baroque funerary and mourning ritualism.
Keywords: engraving; funeral; Kyiv-Pechersk lavra; procession; baroque; Fedor Golovin